Development Status and Prospects of Artificial Intelligence in the Field of Energy Conversion Materials - Yang, Xinyi; Luo, Ziyi; Huang, Zihan; Zhao, Yihang; Xue, Zhichang; Wang, Yingxue; Liu, Weidi; Liu, Siliang; Zhang, Hong; Xu, Kui; Dou, Shuming; Xu, Jie; et al. (Frontiers in Energy Research, 2020)
With the characteristics of high-speed calculation and high-accuracy prediction, artificial intelligence (AI) which also known as machine intelligence, including deep learning, machine learning, etc., have shown great advantages in cross-field applications. In material science field, AI can be used to discover new materials and predict corresponding critical properties. At present, AI has been used in the exploitation of energy conversion materials and other energy-related materials. In this review, we summary the current achievements of AI applications in energy conversions, analyze the advantages and disadvantages of AI techniques in material researches and point out future development prospects.